Polysalicylic Acid Polymer Microparticle Decoys Therapeutically Treat Acute Respiratory Distress Syndrome. Issue 7 (17th December 2021) - Brannon, Emma R.; Kelley, William J.; Newstead, Michael W.; Banka, Alison L.; Uhrich, Kathryn E.; O'Connor, Colleen E.; Standiford, Theodore J.; Eniola‐Adefeso, Omolola
Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) remain problematic due to high mortality rates and lack of effective treatments. Neutrophilic injury contributes to mortality in ALI/ARDS. Here, technology for rapid ARDS intervention is developed and evaluated, where intravenous salicylic acid‐based polymer microparticles, i.e., Poly‐Aspirin (Poly‐A), interfere with neutrophils in blood, reducing lung neutrophil infiltration and injury in vivo in mouse models of ALI/ARDS. Importantly, Poly‐A particles reduce multiple inflammatory cytokines in the airway and bacterial load in the bloodstream in a live bacteria lung infection model of ARDS, drastically improving survival. It is observed that phagocytosis of the Poly‐A microparticles, with salicylic acid in the polymer backbone, alters the neutrophil surface expression of adhesion molecules, potentially contributing to their added therapeutic benefits. Given the proven safety profile of the microparticle degradation products—salicylic acid and adipic acid—it is anticipated that the Poly‐A particles represent a therapeutic strategy in ARDS with a rare opportunity for rapid clinical translation. Abstract : In this work, polymeric microparticles are fabricated from a salicylate‐based polymer (Poly‐A) and investigated as a therapeutic for acute inflammation of the lungs. This particle formulation performs exceptionally well in diverting neutrophils away from the lungs, ultimately reducing inflammatory‐based damage. Furthermore, Poly‐A particles are observed to change the neutrophil surface expression of inflammatory molecules.